A sliding mode controller for aircraft simulated entry into spin - Rao, D. M. K. K. Venkateswara. (2013)
In this paper, two controllers are presented for commanded departure of an aircraft into spin. The first controller is designed based on the information obtained from the bifurcation analysis results of the aircraft model and trial and error simulation experiments. The second controller is a nonlinear sliding mode controller also designed using bifurcation analysis results of the aircraft as reference maps. The sliding mode controller design problem is formulated as a trajectory tracking problem, where, the reference trajectory to be tracked is defined by spin simulation. Initial conditions are level-flight trim states, computed using extended bifurcation analysis and final states are stable, steady and flat oscillatory spin states.